Does pre-operative urodynamics lead to better outcomes in management of urinary incontinence in women? A linked systematic review and meta-analysis. (January 2020) - Lor, Kar Yee; Soupashi, Maria; Abdel-Fattah, Mohamed; Mostafa, Alyaa
Abstract: The use of preoperative urodynamics as a standard investigation for urinary incontinence (UI) has long been a subject of debate, with a lack of robust evidence to demonstrate improved patients' outcomes. We aim to compare the clinical and cost effectiveness of urodynamics versus office clinical evaluation only, prior to the treatment of UI. We conducted three linked systematic reviews and meta-analyses of randomised controlled trials (RCTs) comparing urodynamics assessment versus clinical evaluation only in women prior to 1) non-surgical treatment of UI, 2a) surgical treatment of stress urinary incontinence (SUI) and 2b) invasive treatment for overactive bladder (OAB). Women with severe pelvic organ prolapse, previous continence surgery and neuropathic bladder were excluded. Primary outcomes were patient-reported and objective success post-treatment. Secondary outcomes were adverse events, quality of life, sexual function and health economic measures. We searched MEDLINE, Embase and Cochrane Central Register of Controlled Trials databases for each category, which was last updated on January 2019. Study selection, risk of bias assessment and data extraction were performed independently by two reviewers. The random effects model was used to assess risk ratio and mean difference with 95% confidence interval. Statistical heterogeneity was assessed by I 2 statistics and the quality of evidence by the Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) approach. Four RCTs compared urodynamics versus clinical evaluation only prior to non-surgical management of UI. Treatment consisted of pelvic floor muscle training, with or without pharmacological therapy. Meta-analysis of 150 women showed no evidence of significant difference in the patient-reported and objective success rates between groups (P = 0.520, RR: 0.91, 95% Cl 0.69–1.21, I 2 = 0% and P = 0.470, RR:0.87, 95% Cl 0.59–1.28, I 2 = n/a, respectively). Seven RCTs were identified for surgical management of SUI. The majority of women underwent mid-urethral tape procedures (retropubic or transobturator approach). Meta-analysis of 1149 women showed no evidence of significant difference in patient-reported (P = 0.850, RR:1.01, 95% CI 0.88–1.16, I 2 = 53%) and objective success between groups (P = 0.630, RR:1.02, 95% CI 0.95–1.08, I 2 = 28%). There was no significant difference in incidence of voiding dysfunction, de novo urgency, and urinary tract infection between groups. No RCTs were identified for invasive management of OAB. In conclusion, limited evidence shows that routine urodynamics prior to non-surgical management of UI or surgical management of SUI is not associated with improved treatment outcomes, when compared to clinical evaluation only. Well-designed clinical trials are needed to evaluate the clinical and cost-effectiveness of routine urodynamics prior to surgical management of SUI and OAB.